1998
DOI: 10.1038/sj.onc.1201616
|View full text |Cite
|
Sign up to set email alerts
|

The DNA binding domains of the WT1 tumor suppressor gene product and chimeric EWS/WT1 oncoprotein are functionally distinct

Abstract: The t(11; 22)(p13; q12) translocation associated with desmosplastic small round cell tumor results in a chimeric molecule fusing the amino terminal domain (NTD) of the EWS1 gene to three of the four carboxyterminal zinc ®ngers of the WT1 tumor suppressor gene. Since the DNA binding domains of WT1 and EWS/WT1 are structurally di erent, we have assessed the functional consequences of the EWS/WT1 fusion. We ®nd that the EWS/WT1 protein has a higher binding a nity for a given recognition target than the WT1 produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 25 publications
3
32
1
Order By: Relevance
“…Similar to the present study no eect of wild type WT1 could be detected on the expression of PDGFA and a number of other putative target genes. Most recently, Kim et al (1998) have shown that DNA binding by the EWS-WT1 fusion protein is much stronger compared to wild type WT1, providing additional evidence for distinct functions of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the present study no eect of wild type WT1 could be detected on the expression of PDGFA and a number of other putative target genes. Most recently, Kim et al (1998) have shown that DNA binding by the EWS-WT1 fusion protein is much stronger compared to wild type WT1, providing additional evidence for distinct functions of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Alternatively, the fusion protein may also ctivate target genes that are not regulated by wild-type WT1 due to changes in the DNA binding domain. 12 A previous in vitro study has shown that PDGF-A was upregulated by EWS-WT1 in desmoplastic small round cell tumor specimens as well as in an inducible cell line. 9 Expression of PDGF-A, a potent mitogen and growth factor for fibroblasts, has been speculated to play a role in the characteristic tumor-associated desmoplasia in desmoplastic small round cell tumor, the extent of which varies from case to case.…”
mentioning
confidence: 96%
“…However, EWS/WT1 downregulation did not correlate with rapamycin-induced apoptosis, suggesting that the known targets of this aberrant transcription factor are most likely not involved in the apoptotic process induced by rapamycin. In agreement with its distinct DNA-binding specificity relative to WT1 (Kim et al, 1998a), microarray analysis has shown that several apoptosis-related genes are regulated by EWS/ WT1 (ÀKTS) (Ito et al, 2003). Interestingly, the normal WT-1 protein is also expressed in DSRCT (Ladanyi and Gerald, 1994), and its activity is believed to be overcome by the stronger activity of EWS/WT1 (Scharnhorst et al, 2001).…”
Section: Discussionmentioning
confidence: 95%